Польские и русские глаголы, мотивированные названиями напитков - Gasz, Agnieszka (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
The article attempts to provide a description of words motivated by names of drinks in Polish and Russian. Comparative research has been conducted on the basis of material excerpted from dictionaries (explanatory dictionaries, dictionaries of synonyms as well as slang and jargon dictionaries). In the course of linguistic analysis the author established main ways of motivating verbs denoting various kinds of consumption and indicated crucial similarities and differences between the two languages.
Keywords: глагол; название напитка; разговорный стиль; польский язык; русский язык; verb; name of drink; informality; Polish language; Russian language